Islamization of knowledge through the al-hidabi model : transforming education towards ummatic excellence - Mohadis, Hazwani Mohd (KICT Publishing, 2025)
The International Institute of Islamic Thought East and Southeast Asia (IIIT ESEA) successfully organized IIIT-TMP Workshop Series on Integrating Islamic Perspectives from 7 to 8 November 2025 at The Chateau Spa & Wellness, Berjaya Hills, Pahang. The workshop involved 15 grant recipients of the IIIT Textbook Materials Project (IIIT-TMP) 2024, with the aim of guiding authors in embedding the Islamization of Knowledge (IoK) approach into their textbook development.